Synthesis of highly substituted N-(Furan-3-ylmethylene)benzenesulfonamides by a gold(I)-catalyzed oxidation/1,2-alkynyl migration/cyclization cascade - Wang, Tao; Huang, Long; Shi, Shuai; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
A variety of N-(furan-3-ylmethylene)benzenesulfonamides were obtained by a gold(I)-catalyzed cascade reaction from easily accessible starting materials. The reaction pathway involves a rarely observed 1,2-alkynyl migration onto a gold carbenoid. This observation further enriches gold carbenoid chemistry with regard to group migration.